Dried herbs and spices : a packaging manual (ITC GenevaCH, 1992)
Reviews products and relevant packaging standards. Explains various types of packaging methods and packaging materials used for handling and storing dried herbs and spices. Outlines current trends in retail packaging. Highlights health, safety and environmental issues affecting spice packaging.
DC